(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
The aim of this paper is to evaluate the financial performance of pension funds in Croatia. Although there are other factors which are important in the pension funds overall performance, this paper focuses on investment accomplishments. The purpose of measuring portfolio performance is to determine whether portfolio managers add value compared to passive investment strategies. The traditional approach to pension funds’ performance evaluation underlines standard measures of financial performance (e.g. ratios such as Sharpe’s, Sortino’s, Treynor’s, etc.) which quantify the ability of pension fund managers to deliver an active management risk premium, with respect to benchmarks. In this paper, the previously mentioned traditional measures of risk-adjusted performance are applied to Croatian pension funds. Due to recent changes in pension systems in other Eastern European countries once again emphasis is put on this issue in Croatia. The analysis furthermore includes evaluation of pension funds’ asset allocation. The period of analysis covers twelve years, from the establishment of pension funds in Croatia in 2002 until 2013. The main hypothesis of the paper states that Croatian pension funds underperform with respect to benchmark comparisons, set as return on the combined CROBEX/CROBIS portfolio. Results show that the main hypothesis does not hold. The financial performance of pension funds directly influences their competitiveness, derived from the possibility of measuring their success in active portfolio management. In addition, pension funds are expected to support the national economy. By investing their accumulating assets, they can protect jobs and enhance economic growth. However, they can achieve that only if they are competitive in means of financial performance.